Refrigerated warehouses as intelligent hubs to integrate renewable energy in industrial food refrigeration and to enhance power grid sustainability. (February 2017) - Fikiin, Kostadin; Stankov, Borislav; Evans, Judith; Maidment, Graeme; Foster, Alan; Brown, Tim; Radcliffe, Jonathan; Youbi-Idrissi, Mohammed; Alford, Adrian; Varga, Liz; Alvarez, Graciela; Ivanov, Ivan Evg.; et al.
Abstract: Background: Independence from fossil fuels, energy diversification, decarbonisation and energy efficiency are key prerequisites to make a national, regional or continental economy competitive in the global marketplace. As Europe is about to generate 20% of its energy demand from Renewable Energy Sources (RES) by 2020, adequate RES integration and renewable energy storage throughout the entire food cold chain must properly be addressed. Scope and approach: Refrigerated warehouses for chilled and frozen foods are large energy consumers and account for a significant portion of the global energy demand. Nevertheless, the opportunity for RES integration in the energy supply of large food storage facilities is often neglected. In situ power generation using RES permits capture of a large portion of virtually free energy, thereby reducing dramatically the running costs and carbon footprint, while enhancing the economic competitiveness. In that context, there exist promising engineering solutions to exploit various renewables in the food preservation sector, in combination with the emerging sustainability-enhancing technology of Cryogenic Energy Storage (CES). Key findings and conclusions: Substantial research endeavours are driven by the noble objective to turn the Europe's Energy Union into the world's number one in renewable energies. Integrating RES, in synchrony with CES development and proper control, is capable of both strengthening the food refrigeration sector and improving dramatically the power grid balance and energy system sustainability. Hence, this article aims to familiarise stakeholders of the European and global food preservation industry with state-of-the-art knowledge, know-how, opportunities and professional achievements in the concerned field. Highlights: Food refrigeration should take advantage of advanced renewable energy technologies. Efficient integration of renewables crucially depends on the energy storage modes. Food cold stores are perfect to enhance the efficiency of cryogenic energy storage. Refrigerated warehouses may act as interactive energy hubs within the power grids.